Long‐pulsed 1064‐nm neodymium:yttrium–aluminum–garnet laser treatment for refractory warts on hands and feet. Issue 3 (10th February 2014) - Kimura, Utako; Takeuchi, Kaori; Kinoshita, Ayako; Takamori, Kenji; Suga, Yasushi
Abstract Common warts (verruca vulgaris) are the most commonly seen benign cutaneous tumors. However, warts in the hands and feet regions often respond poorly to treatment, some are resistant to more than 6 months of treatment with currently available modalities, including cryotherapy, being defined as refractory warts. We investigated the usefulness of long‐pulsed neodymium:yttrium–aluminum–garnet (LP‐Nd:YAG) treatment for refractory warts. The clinical trial was conducted on 20 subjects (11 male, nine female) with a total of 34 lesions (periungual/subungual areas, plantar areas, fingers and/or toes). All the subjects suffered from refractory warts despite conventional treatments for more than 6 months. The patients were administrated up to six sessions of treatment, at intervals of 4 weeks between sessions, with an LP‐Nd:YAG at a spot size of 5 mm, pulse duration of 15 msec and fluence of 150–185 J/cm2. Evaluation of the treatment results at 24 weeks after the initial treatment showed complete clearance of the refractory warts in 56% of the patients. Histological evaluation showed separation of the dermis and epidermis at the basement membrane with coagulated necrosis of the wart tissue in the lower epidermis, as well as coagulation and destruction of the blood vessels in the papillary dermis following the laser irradiation. No scarring, post‐hyperpigmentary changes or serious adverse events were documented. Our preliminary results show that LP‐Nd:YAG treatments are safe and effective for refractory warts of hands and feet, causing minimal discomfort, and is a viable treatment alternative.